The sociological interpretation of the New Testament : perspectives on the parables : Luke 16:1-8a - Combrink, Hans Jacob Bernardus (Stellenbosch : Stellenbosch University, 2012)
Dissertations (B. Th.) -- University of Stellenbosch, 1994.